On-Demand Culture : Digital Delivery and the Future of Movies - Tryon, Chuck, 1970- (Book collections on Project MUSE., 2013)
The movie industry is changing rapidly, due in part to the adoption of digital technologies. Distributors now send films to theaters electronically. Consumers can purchase or rent movies instantly online and then watch them on their high-definition televisions, their laptops, or even their cell phones. Meanwhile, social media technologies allow independent filmmakers to raise money and sell their movies directly to the public. All of these changes contribute to an "on-demand culture," a shift that is radically altering film culture and contributing to a much more personalized viewing experience. Chuck Tryon offers a compelling introduction to a world in which movies have become digital files. He navigates the complexities of digital delivery to show how new modes of access-online streaming services like YouTube or Netflix, digital downloads at iTunes, the popular Redbox DVD kiosks in grocery stores, and movie theaters offering digital projection of such 3-D movies as Avatar-are redefining how audiences obtain and consume motion picture entertainment. Tryon also tracks the reinvention of independent movies and film festivals by enterprising artists who have built their own fundraising and distribution models online. Unique in its focus on the effects of digital technologies on movie distribution, On-Demand Culture offers a corrective to address the rapid changes in the film industry now that movies are available at the click of a button.